Dermatological Complications of Circumcision: Lesson Learned from Cases In a Pediatric Dermatology Practice. Issue 5 (20th May 2013) - Tempark, Therdpong; Wu, Tim; Singer, Craig; Shwayder, Tor
Abstract We discuss 11 cases of boys who presented with dermatologic complications of circumcision in an outpatient pediatric dermatology clinic. A medical practitioner had previously circumcised all patients during the newborn period. The majority of cases were found incidentally during initial thorough dermatologic examination. Late cutaneous complications included penile skin bridge, glandular adhesion of remnant foreskin, concealed penis, and a penile epidermal inclusion cyst. Minor surgical procedures under local anesthesia were performed in all but two cases. These cases should help dermatologists recognize the common late cutaneous complications of male newborn circumcision and provide insight into potential options for early intervention and management.